КЛИНИЧЕСКОЕ ТЕЧЕНИЕ И ИСХОДЫ ХРОНИЧЕСКОЙ ДЕЛЬТА-ИНФЕКЦИИ В ЭНДЕМИЧНОМ РЕГИОНЕ - Л. Ю. Ильченко; Т. В. Кожанова; А. А. Сарыглар; Я.-Н. Д.; О. Н. Сарыг-Хаа; Р. М. Соян; Ю. П. Зубков; О. В. Исаева; К. К. Кюрегян; М. И. Михайлов (SINAPS LLC, 2012)
Total 214 patients with delta infection were examined. Total 48 patients were followed annually during the observation period (2009-2011). Diagnosis of chronic hepatitis delta (CHD) was established in 78,6% (162/206) cases, liver cirrhosis (LC) - in 21,4% (44/206). HDV RNA was detected in 26,2% (56/214) patients. HDV was genotype I. Progression of CL was observed among 31,3% (15/48) of followed patients, decompensation of CL - in 8,3% (4/48), hepatocellular carcinoma - in 4,2% (2/48) cases; mortality was 29,2% (14/48), with hepatic coma and bleeding from esophageal varices as the main cause of death.